Pengembangan Formula Gel Ekstrak Teh Hijau (Camellia sinensis L.) sebagai Penyubur Rambut - Yety Lindawati, Novena; Murtisiwi, Lusia; C.E. Dhurhania (Jurnal Farmasi (Journal of Pharmacy), 2014)
Hair loss is can be a fashionable matter. Green tea extract which the concentration is about 5% can stimulate hair growing (Sumakdjaja, et.al.,2008). The compound in green tea extract are catecine and their derivate. They are epicatecine (EC), epicatecine galat (ECG), and epigalocatecine (EGCG). In green tea axtract there are also contains galat acid, galocatecine galat (GCG), galocatecine (GC), catecine galat (CG), catecine (C), vitamin B and vitamin C (Agus, 2007) which can make hair root stronger, prefent hair loss, to inhibit free radical, neutralize poisson, and protect head skin from infection. People more interest to use cosmetics and foods with green tea extract. There is no hair growth stimulating gel with green tea extract in the market. This is the reason of this research, is to develope hair growth stimulating gel formula. There are four formula in this research. They are formula I (Carbopol 1%, TEA0 3%, and glycerine 1%), formula II (CMC Na 3% and glycerine 1%), formula III (PEG 400 72%, PEG 4000 8%, and glycerine 1%) and formula IV (carbopol 0,75%, TEA 2%, PEG 400 12%, and glycerine 1%). The concentration of green tea axtract in each formula are 5%. In each formula contains 0,1% nipagin as a preservative, and 0,1% sodium metabisulfit. The quality of each gel formula tested by organoleptic test, homogenity test, pH test, spread test, thickening test, protection test, primary iritation test, aceptability test, and hair growth stimulating activity test.